The life scenarios of family who have autistic child at home - Cau Kim Jiu; Somporn Rungreangkulkij (Journal of Health Technology Assessment in Midwifery, 2019)
Living with autism is not easy for the autistic children themselves and their family members. Especially the family members who are also the main caregivers. This ethnographic study aimed to describe the ways of life of families who have children with autism at home. Data were collected through participant observations, focus group discussions and in-depth interviews. There were 20 families as key informants taken by purposive sampling who consist of mothers, grandmothers, and siblings. The data were analyzed by thematic analysis. There were four family life scenarios of family living with autistism including: 1) basic self care activity, 2) locking doors to protect the autistic children, 3) woman act as a main caregiver, 4) risk of child abuse, and 5) supporting from spouse and other family members. Main caregivers risk psychological, physical and social problems. Nurses should provide counseling to the main caregiver by deep listening to their concerns and teaching them how to manage stress. In addition, caregivers need supports from the family member particularly the husband.